PATTERN OF FARMING PRACTICES AND SUSTAINABLE AGRICULTURAL DEVELOPMENT: A STUDY ON THE LINKAGE - Baksh, S. Allah; Rajkumar, P.; Sankaran, A. (ASIAN JOURNAL FOR POVERTY STUDIES (AJPS), 2017)
Agricultural development is the sine qua non for socio-economic development of a nation in general and developing countries in particular. The sustainable agriculture can be traced that it enhances the environmental quality and the resource base upon which agriculture depends. This form of agriculture is expected to provide basic human food and other major needs which are socially desirable and economically viable. This awareness has come to the centre stage of global debate as a result of degradation of natural resources and environment. The present study is an attempt to examine the farming practices in Cuddalore district of Tamil Nadu, India. The study is an empirical investigation based upon the data collected from the above mentioned field. The data were collected from 335 respondents of the district who were selected through multi-stage stratified random sampling method. In the first phase one developed taluk, a backward taluk, and a most backward taluk were identified. In the second phase one community development block is selected from each taluk. Third phase is the selection of five villages from each block. And at the final stage from each village 10 per cent of the farm households were selected at random. From the selected respondents the data were collected by using the tool of interview-schedule. The farming pattern of each educational group is associated with the views on advantages of cultivating traditional crop variety and the awareness of impact of chemical fertilizer on land and crops.